The Effects of Sleep on Emotional Target Detection Performance: A Novel iPad-Based Pediatric Game - Colonna, Annalisa; Smith, Anna B.; Smith, Stuart; VanDenEshof, Kirandeep; Orgill, Jane; Gringras, Paul; Pal, Deb K. (Frontiers in Psychology, 2018)
Background: Consolidation of learning occurs during sleep but when it is disturbed there may be an adverse impact upon these functions. While research has focused upon how sleep affects cognition in adulthood, the effects of disrupted sleep are likely to impact more heavily on learning among children and adolescents. We aimed to investigate whether a night’s sleep impacts upon executive function compared with an equivalent wakefulness period. We also wanted to know whether restricting sleep would reduce these effects on performance. To investigate this issue in children, we adapted existing research methods to make them more suitable for this population. Methods: Using a cross-over trial design, twenty-two children aged 7-14 completed an updated but previously validated, continuous performance task (CPT) designed to be appealing to children, containing emotional and neutral targets and presented on an iPad. We measured omission and commission errors, mean and variability of reaction times immediately and after a delay spent in the following three ways: 11-hour intervals of unrestricted and restricted sleep in the style of a ‘sleepover’ and daytime wakefulness. We examined differences in immediate and delayed testing for each dependent variable. Both sleep nights were spent in a specialist sleep lab where polysomnography data were recorded. Results: While there were no significant main effects of sleep condition, as expected we observed significantly faster and more accurate performance in delayed compared with immediate testing across all conditions for omission errors, reaction time and variability of reaction time. Importantly, we saw a significant interaction for commission errors to emotional targets (p=.034): while they were comparable across all conditions during immediate testing, for delayed testing there were significantly more errors after wakefulness compared with unrestricted sleep (p=.019) and at a trend level for restricted sleep (p=.063). Performance improvement after restricted sleep was inversely correlated with sleep opportunity time (p=.03), total sleep time (p=.01) and total non-REM time (p=.005). Conclusions: This tool, designed to be simple to use and appealing to children, revealed a preserving effect of typical and disrupted sleep periods on performance during an emotionally themed target detection task compared with an equivalent wakefulness period.